From social rights to the market: neo-liberalism and the knowledge economy - Holmwood, John (Routledge, 2014)
Public higher education has a long history, with its growth associated with mass higher education and the extension of a social right to education from secondary schooling to university education. Following the rise in student numbers since the 1970s, the aspiration to higher education has been universalized, although opportunities remain structured by social background. This paper looks at changing policies for higher education in the UK and the emergence of a neoliberal knowledge regime. This subordinates higher education to the market and shifts the burden of paying for degree courses onto students. It seeks to stratify institutions and extend the role of for-profit providers. From a role in the amelioration of social inequality, universities are now asked to participate actively in the widening inequalities associated with a neoliberal global market order.